Zonasi Bencana Abrasi Pantai Sappoang Kabupaten Polewali Mandar - Hamsah Hamsah; Nirmawala Nirmawala (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2022)
This research uses a formula approach. In formula has several variables. The variables in this research are tidal, ocean current speed and direction, wave height and wave period, type of geological structure of the coast and sediment grain size materials, the slope of the beach and coastline direction, wind speed and direction. The number of samples or observation points at 27, with interval distance every point is 200 m. The results of the research were analyzed in the waves of the type formula and determinants of abrasion and sedimentation. Sappoang Beach is one of the marine landforms are more specifically known as a land form bar (deposition of sand along the coast). Conditions beach located around the mouth of the river to the beach physical differences that are in the basin area (central coast), where the force of the waves, and the flow velocity at the beach slope basin area beaches have greater value when compared to the coastal areas near the mouth river. The results showed that there are three conditions in Sappoang Beach beaches of different areas of research currently conducted (the west wind), like sedimentation area, balanced and abraded. Abraded zone and sedimentation zone is more dominant than the beaches that are stable. This is more significant because at the time of measurement, the wind is blowing west wind, given the quantity of variables measuring the higher the coast, so the coastal zone is increasing abraded.